Mongolia : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2003)
The report provides the details of the assessment on Mongolia's Poverty Reduction Strategy Paper. It describes the Economic Growth and Poverty Reduction Strategy (EGPRS), which presents main policy directions of the government with a focus on economic growth acceleration and poverty reduction efforts. It describes the transition period of Mongolia, demographic trends drawn from the household income and expenditure survey, the poverty situation, gender inequality, and poverty reduction strategy. It also reviews the promotion of economic and financial stability and provides a strategy for monitoring the policies.